SiO2 Coated on ZnO Nanorod Arrays With UV-Durable Superhydrophobicity and Highly Transmittance on Glass - Li, Hong; Zou, Xinyan; Wei, Hongyan; Li, Qiang; Gao, Qiang; Liu, Qinzhuang; Zhang, Jinfeng (Frontiers in Chemistry, 2020)
ZnO nanorod arrays were fabricated on glass through hydrothermal way. Then a thin SiO2 film were covered on ZnO nanorod arrays using pulsed laser deposition (PLD) technique, and modified by stearic acid. It is found that SiO2 film only had slight effects on the contact angle and transmittance of ZnO nanorod arrays on glass substrate. However, it has brought a huge improvement in the UV durability of superhydrophobic ZnO nanorod arrays. The results showed that the water contact angle remains constant at 160.5o even UV irradiation time exceeded 50 h when the deposition time of PLD is about 10 min. This structure with UV-durable superhydrophobicity and highly transmittance on glass substrate can be served as front materials in solar cells.